Desertification of drylands in Northeast of Brazil - Lemos, José de Jesus Sousa (1995)
In general we observe that the natural and planted vegetal cover of the Semi-Arid of Northeast of Brazil is desapearing at a very fast rate. We observe that this region presents a grave problem of sustainability or resilience in the production of bean, corn and cattle. A previous study, Lemos (1995a) has showed that in aggregated terms, the agricultural production of the Northeast is not sustainable. When we disaggregate the data at municipality level we have an exact dimension of the problem and of its localization. Because of their characteristics, most of the municipalities situated in the Semi-Arid zone of this region show some level of desertification. As we have seen, desertification is caused in part by the behavior of man. The behavior of man can also stop the process, by using the natural resources in a sustainable way. This implies in a strong change in the way agricultural activities are practiced in this region. We have shown in previous study (see Lemos, 1995b) that this region has a great vocation to produce fruits. The rational utilization of the land, must be by using a planned diversified exploitation, because monoculture is dangerous to biodiversity and can induce a very high level of economic risk (see Horowite, 1988). The plantation of these kind of trees and a planned reforestation with native species could give to the soil the natural protection against the direct incidence of the sunlight, and it can also protect the soil against the erosion caused by the storms which occurs in the rainfall season (Dixon, 1988). This could help to bring back the native fauna which is disapearing because the chart we just showed in this research. In the next chapter of this research we will show how the desertification process have affected the areas and the population of the States and of the Northeast itself